Effects of filler metals on the segregation, mechanical properties and hot corrosion behaviour of pulsed current gas tungsten arc welded super-austenitic stainless steel. (October 2016) - Devendranath Ramkumar, K.; Chandrasekhar, Aditya; Srivastava, Anubhav; Preyas, Hidad; Chandra, Sanskar; Dev, Sidharth; Arivazhagan, N.
Graphical abstract: Highlights: Effect of fillers on the Mo-segregation during PCGTA welding of AISI 904L. Segregation was minimized while employing Ni-Mo rich fillers. Hot corrosion studies in the molten salt environment at 650 °C are investigated. Studies recommended the use of ERNiCrMo-14 filler for joining AISI 904L. Abstract: Segregation of Mo is one of the most detrimental problems associated with the welding of super-austenitic stainless steels. The present study articulates the effects of fillers on the microstructure and mechanical properties of pulsed current gas tungsten arc (PCGTA) welded joints of AISI 904L. Four different fillers namely ERNiCrMo-4, ERNiCrMo-10, ERNiCrMo-14 and ERNiCu-7 were employed for joining 5 mm thick plates of AISI 904L. Efforts had been taken to investigate the effect of filler wires on the segregation of Mo in the fusion zone. Studies attested to the retention of Mo in the dendritic regions while employing Ni-Mo rich fillers. Evidently, Mo in the fusion zones was comparatively greater than that in the parent metal. Microstructure studies revealed the formation of unmixed zones at the weld interface while employing these fillers. Migrated grain boundaries were prominent in the fusion zone of ERNiCu-7 weldments. Tensile studies demonstrated that failures occurred at the parent metal of AISI 904L irrespective of fillers employed. Charpy V-notch studies showed that the impact toughness at the cap zones of the weldments was superior to the root regions for all the cases of the weldments. Also, the welded coupons were subjected to cyclic hot corrosion studies at 650 °C in a synthetic molten salt mixture containing K2 SO4  + 60% NaCl for 50 cycles. The corrosion studies attested that the fusion zone employing ERNiCrMo-14 exhibited better corrosion resistance than the other fillers and also the parent metal employed in the study. Surface analytical techniques were employed to investigate the hot corroded species.